The Effects of Monetary Policy Surprises and Fiscal Sustainability Regimes in the Euro Area - António Afonso; José Alves; Serena Ionta (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the effect of monetary surprise shocks on real output and the price level, conditioned on different fiscal sustainability regimes in the period 2001Q4-2021Q4. First, we estimate time-varying fiscal sustainability coefficients based on Bohn's (1998) approach through Schlicht's (2003) method. Then, by taking these sustainability coefficients in a nonlinear local projection model for the Euro Area (aggregate data), Germany, Italy, and Portugal, we analyze the interaction between both policies under (un)sustainable fiscal regimes. Our results show that in a Ricardian regime, output and prices respond to monetary tightening by contracting, while in a non-Ricardian regime the effect on output and price levels is negligible (or even positive). The dependence of the effectiveness of monetary policy on fiscal solvency is valid for Euro-Area and all the countries assessed, and does not depend on whether a country is "core" or "periphery", but on the policy conduct over time.
Keywords: C32; E58; E62; E63; 330; monetary surprises; fiscal sustainability; local-projection models; fiscal-monetary policy mix; Euro area; Germany; Italy; Portugal